CONTRIBUTION INDEX OF MADRASAH DINIYAH TO THE CHARACTER EDUCATION - Ikhrom, Ikhrom; Junaedi, Mahfud; Ismail, Ahmad (Analisa: Journal of Social Science and Religion, 2019)
Madrasah diniyah is acknowledged as the oldest educational institution that pioneered character education in Indonesia. Therefore, should there is a policy in relation to the dissolution of madrasah diniyah, public responses are emerging to reject the policy. This study reveals two pivotal roles of madrasah diniyah in relation to character education. First, the contribution of madrasah diniyah to the character education program in Central Java. Second, the contribution index of madrasah diniyah to the character education program in Central Java. This is a descriptive quantitative research. The data obtained through questionnaires by using random sampling technique and interviews. Index contribution is measured through an average score of the respondent’s answer. The contribution index is divided into five categories, namely, extreme high, high, medium, low, and extreme low. This research found out that madrasah diniyah, in general, contributes significantly to the majority of all the character education. It highlights, however, medium contribution in terms of honest character and low contribution with regards to character of fond.